Long‐term outcome of belatacept therapy in de novo kidney transplant recipients – a case‐match analysis. (6th March 2015) - Schwarz, Christoph; Mayerhoffer, Sophie; Berlakovich, Gabriela A.; Steininger, Rudolf; Soliman, Thomas; Watschinger, Bruno; Böhmig, Georg A.; Eskandary, Farsad; König, Franz; Mühlbacher, Ferdinand; Wekerle, Thomas
Summary While belatacept has shown favorable short‐ and midterm results in kidney transplant recipients, only projections exist regarding its potential impact on long‐term outcome. Therefore, we performed a retrospective case‐match analysis of the 14 belatacept patients originally enrolled in the phase II multicenter trial at our center. Fifty six cyclosporine (CyA)‐treated patients were matched according to age at transplantation, first/retransplant, and donor type. Ten years after kidney transplantation, kidney function remained superior in belatacept‐treated patients compared with the CyA control group. Moreover, none of the belatacept‐treated patients had donor‐specific antibodies ≥10 years post‐transplantation compared with 38.5% of tested CyA‐treated subject (0/10 vs. 5/13; P = 0.045). Notably, however, patient and graft survival was virtually identical in both groups (71.4% vs. 71.3%; P = 0.976). In the present single‐center study population, patients treated with belatacept demonstrated a patient and graft survival at 10 years post‐transplant which was comparable to that of similarly selected CNI‐treated patients. Larger studies with sufficient statistical power are necessary to definitively determine long‐term graft survival with belatacept.